Pediatric Population Pharmacokinetic Modeling and Exposure–Response Analysis of Ambrisentan in Pulmonary Arterial Hypertension and Comparison With Adult Data. (29th January 2023) - Okour, Malek; Thapar, Mita M.; Farrell, Colm; Lukas, Mary Ann; Beghetti, Maurice; Beerahee, Misba
Abstract: This study aimed to develop a population pharmacokinetic (PK) model of ambrisentan in pediatric patients (8 to <18 years) with pulmonary arterial hypertension (PAH) and compare pediatric ambrisentan systemic exposure with previously reported adult data. Association of ambrisentan exposure with efficacy (6‐minute walking distance) and safety (adverse events) were exploratory analyses. A population PK model was developed using pediatric PK data. Steady‐state systemic exposure metrics were estimated for the pediatric population and compared with previously reported data in adult patients with PAH and healthy subjects. No covariates had a significant effect on PK parameters; therefore, the final covariate model was the same as the base model. The pediatric population PK model was a 2‐compartment model including the effect of body weight (allometric scaling),  first‐order absorption and elimination, and absorption lag time. Steady‐state ambrisentan exposure was similar between the pediatric and adult population when accounting for body weight differences. Geometric mean area under the concentration‐time curve at steady state in pediatric patients receiving ambrisentan low dose was 3% lower than in the adult population (and similar in both populations receiving high dose). Geometric mean maximum plasma concentration at steady state in pediatric patients receiving low and high doses was 11% and 18% higher, respectively, than in the adult population. There was no apparent association in the pediatric or adult population between ambrisentan exposure and change in 6‐minute walking distance or incidence of ambrisentan‐related adverse events in pediatric patients. The similar ambrisentan exposure and exposure–response profiles observed in pediatric and adult populations with PAH suggests appropriateness of body‐weight–based dosing in the pediatric population with PAH.